Mitochondrial phylogeography and cryptic divergence in the stickleback genus Pungitius. (24th August 2015) - Wang, Cui; Shikano, Takahito; Persat, Henri; Merilä, Juha
Abstract: Aim: Stickleback fish exhibit considerable morphological variation within and between species, and similar armour phenotypes are often found in different taxonomic groups. Although several Pungitius species and subspecies have been recognized, their evolutionary history and relationships remain poorly known. We investigated the phylogenetic relationships and phenotypic divergence in this genus with a particular focus on P. pungitius and P. laevis . Location: Northern Hemisphere. Methods: Nucleotide variation was analysed in five mitochondrial regions (control region, cytochrome b, ATPase 6, 12S rRNA and 16S rRNA) covering a total of 3236 bp in 194 individuals from five recognized species ( P. pungitius, P. laevis, P. platygaster, P. tymensis and P. kaibarae ). Results: Six highly divergent lineages were identified, including those corresponding to P. pungitius, P. platygaster, P. tymensis and P. kaibarae . However, P. laevis was found to be polyphyletic, consisting of three divergent lineages. Two of them were independent monophyletic groups, whereas the third one clustered together with P. pungitius . All of the P. laevis lineages, as well as one P. pungitius lineage, were found in the central and southern parts of France. Divergence within this genus was indicated to have begun about 4.4 Ma in the Pliocene epoch. All divergences in the Western Palaearctic were estimated to have occurred during the Pleistocene (≤ 2.6 Ma). No correspondence was found between the molecular phylogeny and the occurrence of distinct armour phenotypes within this genus. Main conclusions: The results suggest that glacial events during the Pleistocene are likely to have strongly impacted the diversification of this genus in the Western Palaearctic, implying that the central and southern parts of France were important glacial refugia for the ancestral Pungitius fish. It also appears that similar armour phenotypes have evolved independently in different Pungitius lineages, questioning the utility of these traits as diagnostic taxonomic characters.